2016
DOI: 10.1002/bbb.1726
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal cultivation with waste streams and metabolic constraints to triacylglycerides accumulation for biofuel production

Abstract: BUSINESS HIGHLIGHTS 239 Global impacts of the bioeconomy | Missed opportunity | Believing in biofuels | Praising Trump | Funding opportunity available | Utilizing waste | More research into algae | Avoiding iLUC TECHNOLOGY NEWS 242 New yeast strain boosts lipid production | The fresh smell of pinene FEATURE 243 Interactive posters: A valuable means of enhancing communication and learning about productive paths toward sustainable bioenergy ERRATUM 396 Erratum The cover image, by Shijian Ge et al., is based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 164 publications
0
17
0
Order By: Relevance
“…Many toxicity studies have shown that C. vulgaris is usually a preferred test organism, since it has a widespread distribution and it can be found in freshwater ecosystems naturally In addition to being reported as one of the eight most tolerant genera, studies have also shown that rapid growth, efficient organic and nutrient uptake from wastewater, reduced toxicity from wastewater (wastewater treatment), and the dominance of wastewater worldwide, including temperate climates, made Chlorella sp. as the model species …”
Section: Introductionmentioning
confidence: 99%
“…Many toxicity studies have shown that C. vulgaris is usually a preferred test organism, since it has a widespread distribution and it can be found in freshwater ecosystems naturally In addition to being reported as one of the eight most tolerant genera, studies have also shown that rapid growth, efficient organic and nutrient uptake from wastewater, reduced toxicity from wastewater (wastewater treatment), and the dominance of wastewater worldwide, including temperate climates, made Chlorella sp. as the model species …”
Section: Introductionmentioning
confidence: 99%
“…The topics of microalgal cultivation and harvesting do not fall under the purview of this review, as they have been extensively reviewed elsewhere . There are, however, important considerations to bear in mind related to microalgal strain cultivation before discussing lipid extraction approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike a chemical feedstock that is unaffected by its origin, the extraction of microalgal lipids is influenced by biological variables, such as species and cultivation conditions. The choice of microalgal species and growth conditions will also have a large impact on the final lipid content . For example, nitrogen deprivation during growth can increase the lipid content of microalgae at the expense of reduced biomass productivity .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations